FRONTIERS IN CLINICAL DRUG RESEARCH - DEMENTIAVOLUME 1 - ATTA UR-RAHMAN (Frontiers in Clinical Drug Research - Dementia Ser., 2020)
Frontiers in Clinical Drug Research - Dementia is a book series which presents comprehensive reviews about research on Dementia, - the loss of brain function associated with Alzheimer's diseases and other related conditions. The disease affects the parts of the brain that deal with memory, thought, and language. Chapters in each volume focus on drug research with special emphasis on clinical trials, research on drugs in advanced stages of development and cure for dementia and related disorders. This volume includes the following reviews:- Meeting the Challenges of Falls and Hip Fractures in Pe.